Co-Design for Participatory Neurodiversity Research: Collaborating With a Community Advisory Board to Design a Research Study - Anne-Laure Le Cunff; Poppy Ellis Logan; Rhian Ford; Brandon-Lee Martis; Iris Mousset; Jane Sekibo; Eleanor Dommett; Vincent Giampietro (Journal of Participatory Research Methods)
Inclusive research practice characterized by the involvement of neurodivergent people in meaningful roles has been described as a "requirement of excellence" in neurodiversity research. This report describes a co-design process in partnership with a Community Advisory Board undertaken to develop a research study involving neurotypical and neurodivergent students as participants. From the formation of the partnership with seven Community Advisory Board members to the outcomes of the co-design process, this report details the methods associated with each step, as well as the benefits and challenges collated in collaboration with members of the Community Advisory Board. Opportunities for improvement in co-design for participatory neurodiversity research are suggested.